Do remittance flows stabilize developing countries in the aftermath of sovereign defaults? - Immaculate Machasio (Philipps-University Marburg, School of Business and Economics, 2016)
Remittances are transfers of money by foreign workers to their home countries. These remittance flows have been considered a very important source of finance for many developing countries accounting between 5-40% of the recipient country's GDP. This paper empirically examines whether remittance flows stabilize developing countries in the aftermath of sovereign defaults. To this end, we conduct Dynamic System Generalised Method of Moments (GMM) estimation techniques by Arellano and Bover (1995) and Blundell and Bond (1998) taking into account annual data cutting across 81 countries from 1990 - 2010. We find that indeed remittances play a significant role in stabilizing a country which has defaulted on its sovereign debt. The findings of this study exhibit different results for different measures of default episodes. All in all our findings confirm yet another channel through which remittances can have a positive influence on recipient countries' economy since they support the hypothesis that the occurrence of a sovereign default spurs on an upsurge in remittances which play a stabilizing role.
Keywords: C23; F34; H63; 330; Remittances; Sovereign Defaults; Capital Flows; Generalised Methods of Moments